Efficiency of static and computer adaptive short forms compared to full-length measures of depressive symptoms. - Choi SW; Reise SP; Pilkonis PA; Hays RD; Cella D; Choi, Seung W; Reise, Steven P; Pilkonis, Paul A; Hays, Ron D; Cella, David (Quality of Life Research, 2010)
Purpose: Short-form patient-reported outcome measures are popular because they minimize patient burden. We assessed the efficiency of static short forms and computer adaptive testing (CAT) using data from the Patient-Reported Outcomes Measurement Information System (PROMIS) project.Methods: We evaluated the 28-item PROMIS depressive symptoms bank. We used post hoc simulations based on the PROMIS calibration sample to compare several short-form selection strategies and the PROMIS CAT to the total item bank score.Results: Compared with full-bank scores, all short forms and CAT produced highly correlated scores, but CAT outperformed each static short form in almost all criteria. However, short-form selection strategies performed only marginally worse than CAT. The performance gap observed in static forms was reduced by using a two-stage branching test format.Conclusions: Using several polytomous items in a calibrated unidimensional bank to measure depressive symptoms yielded a CAT that provided marginally superior efficiency compared to static short forms. The efficiency of a two-stage semi-adaptive testing strategy was so close to CAT that it warrants further consideration and study.